Compressive stress drives adhesion-dependent unjamming transitions in breast cancer cell migration - Cai, Grace; Nguyen, Anh; Bashirzadeh, Yashar; Lin, Shan-Shan; Bi, Dapeng; Liu, Allen P. (Frontiers in Cell and Developmental Biology, 2022)
Cellular unjamming is the collective fluidization of cell motion and has been linked to many biological processes, including development, wound repair, and tumor growth. In tumor growth, the uncontrolled proliferation of cancer cells in a confined space generates mechanical compressive stress. However, because multiple cellular and molecular mechanisms may be operating simultaneously, the role of compressive stress in unjamming transitions during cancer progression remains unknown. Here we investigate which mechanism dominates in a dense, mechanically stressed monolayer. We find that long-term mechanical compression triggers cell arrest in benign MCF10A epithelial cells and enhances 4T1 cancer cell migration in transitions correlated with cell shape, leading us to examine the contributions of cell-cell adhesion and substrate traction in unjamming transitions. We show that cadherin-mediated cell-cell adhesion regulates differential cellular responses to compressive stress and is an important driver of unjamming in stressed monolayers. Importantly, compressive stress does not induce the epithelial—mesenchymal transition in unjammed cells. Furthermore, traction force microscopy reveals the attenuation of traction stresses in compressed cells within the bulk monolayer regardless of cell type and motility. Interestingly, as traction within the bulk monolayer decreases significantly with compressive pressure, 4T1 cells at the leading edge do not have reduced traction under compression. Together, strengthened intercellular adhesion and attenuation of traction forces within the bulk cell sheet under compression leads to fluidization of the cell layer and may impact collective cell motion in tumor development and breast cancer progression.